DIABETIC FOOT EXERCISE AS AN INTERVENTION TO IMPROVE FOOT HEALTH IN ELDERLY PATIENTS WITH TYPE 2 DIABETES MELLITUS: A STUDY AT PRATAMA PRIMA MELATI CLINIC - Nasution, Ali Napiah; Sri Lestari Ramadhani Nasution; Sri Wahyuni Nasution (International Archives of Medical Sciences and Public Health, 2025)
Diabetic food complications are among the most serious challenges faced by elderly individuals with type 2 diabetes mellitus (T2DM), often leading to reduced mobility, diminished quality of life, and a heightened risk of ulceration. This study evaluated the effectiveness of diabetic foot exercise as a non-pharmacological intervention to improve foot health in older T2DM patients. Using a quasi-xperimental pre-test - post-test design, participants at Pratama Prima Melati Clinic were assigned to either an intervention group or a control group. The control group received standard care, while the intervention group performed structured diabetic foot exercises three times per week for four weeks. Foot health outcomes, including circulation, sensitivity, and range of motion, were assessed using standardized clinical tests before and during the intervention. Results showed that the intervention group demonstrated significant improvements in circulation, neuropathic symptoms, and joint flexibility compared to the control group (p < 0.05). These findings suggest that diabetic foot exercise is an effective strategy to enhance foot health and potentially prevent complications in elderly T2DM patients. Incorporating such exercise programs into primary healthcare practice is strongly recommended to support comprehensive diabetes control management.